Long-term efficacy of sodium-glucose cotransporter 2 inhibitor therapy in preventing atrial fibrillation recurrence after catheter ablation in type 2 diabetes mellitus patients - Hao-Tien Liu; Hung-Ta Wo; Po-Cheng Chang; Hui-Ling Lee; Ming-Shien Wen; Chung-Chuan Chou (Heliyon, 2023)
Background: Sodium-glucose cotransporter 2 inhibitors (SGLT2i) reduce new-onset atrial fibrillation (AF) in patients with type 2 diabetes mellitus (T2DM). We aimed to determine the long-term effects of SGLT2i on atrial tachyarrhythmia recurrence after catheter ablation (CA) in T2DM patients. Methods: This retrospective study enrolled consecutive patients with T2DM undergoing CA for AF between January 2016 and December 2021. Patient baseline demographic characteristics and use of anti-diabetic and anti-arrhythmic medications were analyzed. Echocardiographic parameters were obtained one day and 6 months after CA. Results: Our study population comprised 122 patients (70% paroxysmal AF). The baseline patient characteristics were similar between the SGLT2i-treated group (n = 45) and the non-SGLT2i-treated group (n = 77) except for stroke. At 6-month follow-up, body-mass index (BMI) was significantly decreased and left ventricular ejection fraction (LVEF) was significantly increased only in the SGLT2i group. E/e’ was decreased 6 months after CA in both groups. During a mean follow-up of 33.7 ± 21.6 months, 22 of 122 patients had atrial tachyarrhythmia recurrence. The long-term atrial tachyarrhythmia-free survival rate was significantly higher in the SGLT2i-treated patients, and multivariate analysis revealed that AF type and SGLT2i use were independently associated with atrial tachyarrhythmia recurrence after CA. Conclusion: The use of SGLT2i and AF type were independent risk factors associated with atrial tachyarrhythmia recurrence after CA in T2DM patients with AF. This result was at least partly due to the pleiotropic effects of SGLT2i on BMI reduction and left ventricular function improvement.